Maximum tidal turbine blade loading during waves and corresponding onset flow variation (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal turbines are required to operate at sites where turbulent flows interact with surface waves. Prediction, and mitigation, of wave induced flows on blades is of increasing interest, particularly for designs that require small immersion depths such as turbines that are large relative to the depth or supported near-surface on floating platforms. Loads in such conditions may be assessed with a range of modelling techniques ranging from high-fidelity CFD in which turbulence and wave kinematics interact and turbines represented with an actuator line method, through to rapid engineering tools such as Blade Element Momentum Theory models in which simplified coupling is employed to facilitate assessment of a wide range of conditions. The combination of the depth-decay of wave kinematics, wave frequency and rotor frequency can lead to load variation over a range of frequencies. Furthermore, under some combinations of conditions dynamic stall may also occur along sections of the rotor blade which presents challenges for tools such as actuator methods and BEMT that typically rely on steady lift and drag datasets. To inform comparison to experiments and higher-fidelity modelling tools, blade element moment theory analysis is undertaken of turbine blade loading in a range of wave conditions.Two turbine designs are assessed – based on the geometries of two published experimental studies, each with differing blade-section and for which measurements of loading in waves are available – to identify the onset conditions to the blade which drive maximum loading during a rotation and during a wave-cycle. For long waves maximum loads are close to in-phase with wave kinematics which are nearly uniform across the rotor plane. For shorter waves, the more rapid depth decay leads to maximum loads occurring out of phase with the wave. For intervals local to the maximum load, radial variation of the blade loading and relative flow to the blade is analysed to characterise the blade-scale flow. During a subset of conditions dynamic stall occurs and these ranges inform comparison to higher fidelity models. For the wider range of conditions in the absence of dynamic stall the dependency of predictions on perturbation of the wave-field in the induction region of the turbine, in which particle kinematics shift from the ellipse occurring in unperturbed waves, is evaluated.